The prevalence of common mental disorders among hospital physicians and their association with self-reported work ability: a cross-sectional study - Ruitenburg Martijn M; Frings-Dresen Monique HW; Sluiter Judith K (BMC, 2012)
Abstract Background We studied the prevalence of common mental disorders among Dutch hospital physicians and investigated whether the presence of a mental disorder was associated with insufficient self-reported work ability. Methods A questionnaire was sent to all (n = 958) hospital physicians of one academic medical center, using validated scales to assess burnout, work-related fatigue, stress, posttraumatic stress disorder (PTSD), anxiety and depression. Furthermore, respondents were asked to rate their current work ability against the work ability in their own best period (adapted version of the first WAI item). The prevalence of each common mental disorder was calculated. In addition, odds ratios of reporting insufficient work ability for subjects with high complaint scores compared to physicians with low complaint scores were calculated for each mental disorder. Results The response rate was 51%, and 423 questionnaires were eligible for analysis. The mental disorder prevalence rates were as follows: work-related fatigue 42%, depression 29%, anxiety 24%, posttraumatic stress complaints 15%, stress complaints 15% and burnout 6%. The mean score for self-reported work ability was 8.1 (range 0-10), and 4% of respondents rated their own work ability as insufficient. Physicians with high mental health complaints were 3.5- for fatigue, 5.6- for PTSD, 7.1- for anxiety, 9.5- for burnout, 10.8- for depression and 13.6-fold for stress more likely to report their work ability as insufficient. Conclusions The prevalence of common mental disorders among hospital physicians varied from 6% for burnout to 42% for work-related fatigue. Those physicians with high complaints had significantly 4- to 14 times increased odds of reporting their own work ability as insufficient. This work suggests that to ensure future workers health and patients safety occupational health services should plan appropriate intervention strategies.